Validation of a reduced NO formation mechanism on a flameless furnace fed with H2-enriched low calorific value fuels. (5th November 2018) - Fortunato, Valentina; Mosca, Gabriele; Lupant, Delphine; Parente, Alessandro
Highlights: Flameless combustion of low calorific value fuels is investigated. A reduced NO mechanism derived from a detailed kinetic scheme is validated. The mechanism is obtained for the specific conditions of flameless regime. All the NO formation pathways are included. The reduced mechanism performs extremely well in predicting NO emissions. Abstract: Flameless combustion is a technology that meets the criteria of reducing pollutants and increasing efficiency in the field of energy production. Such combustion regime is also characterized by a large fuel flexibility. The present work aims at validating a reduced NO mechanism on a flameless furnace, fed with coke oven gas and a blend of coke oven gas and blast furnace gas. The reduced mechanism, derived for the specific conditions of flameless combustion regime, includes all the relevant NO formation pathways, including thermal NO as well as N2 O and NNH. Indeed, it is essential to include the unconventional NO formation routes in order to correctly predict the NO emissions, because of the flameless conditions and the high hydrogen content in the fuel. First, the goodness of the physical model adopted has been assessed. The model describes well the behavior of the furnace. Both the temperature and the species concentration in the exhaust gases, as well as the radical OH predictions are in good agreement with the experimental data, for both fuels. The analysis of the performances of the reduced mechanism shows that such reduced mechanism performs significantly better than global schemes, traditionally employed to assess NO emissions in such systems. In particular, the error is doubled when the global schemes are employed to assess the NO emissions for all the different cases analysed.